Near-Quantitative Photothermal Conversion in Non-Fluorescent Diradicaloid Organic Molecules for Efficient Solar Energy Harvesting - Lian, Wenru (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 Wiley‐VCH GmbH.